2010
DOI: 10.1096/fj.10-158972
|View full text |Cite
|
Sign up to set email alerts
|

The active Zot domain (aa 288–293) increases ZO‐1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO‐1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation

Abstract: Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 45 publications
(63 reference statements)
2
74
0
3
Order By: Relevance
“…It was also shown that phosphorylation of Tyr-398 and Tyr-402 prevents the interaction of occludin and ZO-1, dissociating the occludin-ZO-1 complex, thereby destabilizing the TJ barrier in colon carcinoma cell line (Caco-2), fibroblast cell line (Rat-1) or kidney cell lines (MDCK) (Elias et al, 2009). These findings are thus in agreement with other studies illustrating the significance of phosphorylation on the assembly of TJ proteins (e.g., occludin, claudin-5, ZO-1) into TJ fibrils at the TJ barrier in X. laevis oocytes (Cordenonsi et al, 1997(Cordenonsi et al, , 1999, small intestine (Goldblum et al, 2011), or brain endothelial cells (Yamamoto et al, 2008).…”
Section: Nonreceptor Protein Kinases: Focal Adhesionsupporting
confidence: 91%
“…It was also shown that phosphorylation of Tyr-398 and Tyr-402 prevents the interaction of occludin and ZO-1, dissociating the occludin-ZO-1 complex, thereby destabilizing the TJ barrier in colon carcinoma cell line (Caco-2), fibroblast cell line (Rat-1) or kidney cell lines (MDCK) (Elias et al, 2009). These findings are thus in agreement with other studies illustrating the significance of phosphorylation on the assembly of TJ proteins (e.g., occludin, claudin-5, ZO-1) into TJ fibrils at the TJ barrier in X. laevis oocytes (Cordenonsi et al, 1997(Cordenonsi et al, , 1999, small intestine (Goldblum et al, 2011), or brain endothelial cells (Yamamoto et al, 2008).…”
Section: Nonreceptor Protein Kinases: Focal Adhesionsupporting
confidence: 91%
“…3A), which converted zonulin to HP2. As further support for the ability of zonulin to increase vascular permeability in mouse lung, we used AT-1002, which represents a peptide agonist of zonulin with permeability-inducing activity in the small intestine or in monolayers of intestinal epithelial cells (12). Similar to the application of AT-1001 in the previous experiments (Fig.…”
Section: Reduced Ali By Antibody-induced Neutralization Of Zonulinmentioning
confidence: 92%
“…On the other hand, the tryptase released by mast cells upon activation has been shown to induce TJs disassembly through the activation of proteinase-activated receptor-2 of the epithelial cells. [88][89][90] These receptors can modulate enteric neurotransmission, secretion, motility, epithelial permeability, and visceral sensitivity, and are also known to regulate intestinal inflammation. 91 Anatomical contacts between mast cells and enteric nerve fibers have been demonstrated in the human gastrointestinal mucosa and inflammation multiplies these contacts.…”
Section: Permeabilitymentioning
confidence: 99%